Classic adrenal adenoma undergoing necrosis secondary to chemotherapy for pancreatic adenocarcinoma. Issue 6 (17th February 2021) - Nour, Daniel; Alexander, Linda; Sutherland, Tom
Summary: Our patient was a 53‐year‐old male with borderline resectable pancreatic adenocarcinoma who on his initial staging CT and subsequent MRI was found to have an incidental adrenal adenoma. Following completion of six cycles of neoadjuvant chemotherapy over a three‐month period, the patient returned for restaging. The adrenal nodule had increased in size and had undergone necrosis with just a fine cuff of residual viable lesion at the margins. It is thought that chemotherapeutic agents should not lead to significant cell death of an adrenal adenoma, and this produced diagnostic uncertainty. Interestingly, the lesion was subsequently biopsied under CT with histology confirming a classic adrenal adenoma. This rare case challenges our understanding of chemotherapeutic effects on adrenal adenomas, and offers another differential when assessing necrotic adrenal lesions.